Uberland: How Algorithms are Rewriting the Rules of Work - Peticca-Harris, Amanda (Labour / Le Travail, 2020)
The article reviews the book, "Uberland: How Algorithms are Rewriting the Rules of Work," by Alex Rosenblat.